Effect of Ketapang (Terminalia catappa) Leaf Powder on Water Chemical Quality Parameters in Growth Media Asian Redtail Catfish (Hemibagrus nemurus) - Romadia, Isna; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2025)
This research was conducted from June to July 2024 at the Faculty of Fisheries and Marine Sciences, Universitas Riau, Pekanbaru. The purpose of this study was to determine the best dose of ketapang leaf powder (Terminalia catappa) on water chemistry parameters in the growth medium of baung fish fry (Hemibagrus nemurus). The research method used a one-factor Completely Randomized Design with 4 levels of treatment and 3 replicates. P0 (control), the use of ketapang leaf powder at a dose of 0.5 g/L (P1), 1 g/L (P2), 1.5 g/L (P3), and 2.5 g/L (P4). Giving ketapang leaf powder with different doses gives an influence on water chemistry parameters in the growth medium of Asian redtail catfish. P1 with a dose of 0.5 g/L produced the best growth and survival reached 93.33%. Providing good water quality during the study, pH was in the range of 6.53-7.20, DO 4.18-4.21 mg/L, temperature 27-28.67oC. On day 30, the lowest ammonia level was found in treatment P1 at 0.0683.